Iron-deficiency anemia: a review of diagnosis and management - Putu Amanda Widiada (DiscoverSys Inc., 2020)
Background: Anemia is the most common medical problem encountered in daily practice. It is a significant health problem, especially in developing countries that have a high prevalence. Iron-deficiency anemia (IDA) is anemia that arises due to decrease in iron supply for erythropoiesis regarded with lack of iron storage that consequently leads to reduced haemoglobin formation.Aim: This literature review aims to review diagnosis to the management of IDA.Conclusion: IDA has severe and detrimental health effects. Complete history taking, physical examination, and laboratory test need to be done thoroughly to be able to establish the diagnosis of IDA as well as to determine its cause. Currently used therapies include oral iron therapy which is the first-line therapy, intravenous iron therapy, and blood transfusion.Â